Examination of social anxiety at university level students - Ça?lar, Mehmet; Dinçyürek, Sibel; Arsan, Nihan (My University, 2012)
This study aims to find whether there is any significant difference among the variables such as students' social anxiety, gender, academic achievement, family income and educational level of parents. Target study group is composed of 2008-2009 fall semester Eastern Mediterranean University students (n=300). In order to find the level of social anxiety, Palanci and Ozbay (2001) "Social Anxiety Scale" was used. Research findings were analyzed through descriptive statistics and multivariate variance analyze (MANOVA) was used. When the findings of research are analyzed it is found out that there is significant difference between student social anxiety, academic achievement and age. For family income variance, it is found out that there is a significant difference between the subscale of social avoidance and concern about being criticize subscale. For mother's education level, statistically significant difference was found in terms of social avoidance subscale, concern about being criticize subscale and sense of worthlessness subscale. There isn't any statistically significant difference for father's education.
Üni?versi?te ö?renci?leri?ni?n sosyal kaygilarinin anali?zi?
Keywords: Anxiety of being Criticized; Sensation of Worthlessness and Academic Achievement; Social Anxiety; Social Avoidance